2023
DOI: 10.1038/s41522-023-00420-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides uniformis-induced perturbations in colonic microbiota and bile acid levels inhibit TH17 differentiation and ameliorate colitis developments

Abstract: Inflammatory bowel disease (IBD) is associated with gut dysbiosis and can lead to colitis-associated malignancies. Bacteroides uniformis (Bu) regulates animal intestinal homeostasis; however, the mechanism by which it alleviates colitis in mice remains unknown. We investigated the effects of B. uniformis JCM5828 and its metabolites on female C57BL/6J mice with dextran sulfate sodium salt (DSS) induced colitis. Treatment with Bu considerably alleviated colitis progression and restored the mechanical and immune … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Instead, it seemed to influence this process inside the lamina propria, indicating a multifaceted mechanism. 75 The results suggest that Bu or bile acid supplements may have promise as therapeutic interventions for colitis and other conditions characterized by impaired intestinal barrier function. The potential therapeutic efficacy of Bu is attributed to its impact on bile acid metabolism, gut microbiota, and immunological modulation.…”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, it seemed to influence this process inside the lamina propria, indicating a multifaceted mechanism. 75 The results suggest that Bu or bile acid supplements may have promise as therapeutic interventions for colitis and other conditions characterized by impaired intestinal barrier function. The potential therapeutic efficacy of Bu is attributed to its impact on bile acid metabolism, gut microbiota, and immunological modulation.…”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 99%
“…137 This investigation's findings demonstrated that Bu's administration effectively mitigated the advancement of colitis, indicating its potential protective efficacy in the DSS-mouse model. 75 Additionally, the Bu therapy has shown the ability to reinstate the production of mechanical and immunological barrier proteins, which are often disrupted in cases of colitis. 75 This suggests that Bu might help preserve the intestinal barrier's integrity.…”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 99%
See 3 more Smart Citations